MODERN LAXATIVE MEDICATIONS IN PEDIATRIC PRACTICE - T.V. Gasilina; S.V. Bel'mer (Вопросы современной педиатрии)
The most usable medications in pediatric practice are laxative medicaments on the basis of polyethylene glycol (Macrogol 4000) and lactulose. Macrogol 4000 (Forlax) and lactulose have rela tively equal activity, but the first one has more predictable effect (has linear dependence dose–effect), has a beneficial activity in the presence of pain syndrome and mucoprotective activity, stimulates appetite. Significant feature of lactulose is its prebiotic activity, and this is the reason of indistinctive dose–effect dependence, presence of latency time and some adverse events; the rate of last ones is low. Authors make a conclusion that the specialist can make a choice of medication, paying attention to peculiarities of disease in every single patient.Key words: children, laxative medicaments, Macrogol 4000.